The Absence of Sensory Axon Bifurcation Affects Nociception and Termination Fields of Afferents in the Spinal Cord - Tröster, Philip; Haseleu, Julia; Petersen, Jonas; Drees, Oliver; Schmidtko, Achim; Schwaller, Frederick; Lewin, Gary R.; Ter-Avetisyan, Gohar; Winter, York; Peters, Stefanie; Feil, Susanne; Feil, Robert; et al. (Frontiers in Molecular Neuroscience, 2018)
A cGMP signaling cascade composed of C-type natriuretic peptide, the guanylyl cyclase receptor Npr2 and cGMP-dependent protein kinase I (cGKI) controls the bifurcation of sensory axons upon entering the spinal cord during embryonic development. However, the impact of axon bifurcation on sensory processing in adulthood remains poorly understood. To investigate the functional consequences of impaired axon bifurcation during adult stages we generated conditional mouse mutants of Npr2 and cGKI (Npr2fl/fl;Wnt1Cre and cGKIKO/fl;Wnt1Cre) that lack sensory axon bifurcation in the absence of additional phenotypes observed in the global knockout mice. Cholera toxin labeling in digits of the hind paw demonstrated an altered shape of sensory neuron termination fields in the spinal cord of conditional Npr2 mouse mutants. Behavioral testing of both sexes indicated that noxious heat sensation and nociception induced by chemical irritants are impaired in the mutants, whereas responses to cold sensation, mechanical stimulation and motor coordination are not affected. Recordings from C-fiber nociceptors in the hind limb skin showed that Npr2 function was not required to maintain normal heat sensitivity of peripheral nociceptors. Thus the altered behavioral responses to noxious heat found in Npr2fl/fl;Wnt1Cre mice is not due to an impaired C-fiber function. Overall, these data point to a critical role of axonal bifurcation for the processing of pain induced by heat or chemical stimuli.